Ingredient of Biomass Packaging Material and Compare Study on Cushion Properties - Fangyi Li; Kaikai Guan; Peng Liu; Gang Li; Jianfeng Li (International Journal of Polymer Science)
In order to reduce the white pollution caused by nondegradable waste plastic packaging materials, the biomass cushion packaging material with straw fiber and starch as the main raw materials had been synthesized. The orthogonal experiment was used to study the impact of mass ratio of fiber to starch, content of plasticizer, active agent, and foaming agent on the compressive strength of cushion material. Infrared spectrometer and theory of water’s bridge-connection were used to study the hydroxyl groups among the fiber and starch. The results were demonstrated as follows: the mass ratio of fiber to starch had the most significant impact on compressive strength. When the contents of the plasticizer, the foaming agent, and the active agent were, respectively, 12%, 0.1%, and 0.3% and the mass ratio of fiber to starch was 2 : 5, the compressive strength was the best up to 0.94 MPa. Meanwhile, with the plasticizer content and the mass ratio of fiber to starch increasing, the cushioning coefficient of the material decreased first and then increased. Comparing the cushion and rebound performance of this material with others, the biomass cushion packaging material could be an ideal substitute of plastic packaging materials such as EPS and EPE.